Alliteration as a means of characterization of dramatic personae - Onič, Tomaž (ELOPE (Ljubljana), 2006)
Alliteration is usually defined as a repetition of the same initial consonant in consecutive or neighbouring words. Despite its importance for dramatic construction, alliteration is rarely preserved in Slovene translations of dramatic texts. Detailed research into this phenomenon in several British and American plays and their Slovene translations showed that the survival of alliterations in the translation process is mostly random. On the rare occasions when alliteration is preserved, no proof could be found of a clear translation strategy focusing on this linguistic element. Since alliteration in most cases appears not as an isolated language element but rather as one of many important text features, the translator should devise priorities. The purpose of this article is not to urge translators to give alliteration the highest priority, but merely to suggest its inclusion among the features considered. This paper also includes examples of non-preservance of alliteration in translated text illustrating the loss for the text and its implications.
Keywords: aliteracija; dramatika; dramski prevod; karakterizacija; književni prevod; prevajanje